Ogee Crest Weir Head-discharge Relationships - Salmasi , Farzin; Abraham , John (Research Highlights in Science and Technology Vol. 7, 2023)
The objective of this study is to investigate dependency of discharge coefficient (C) in ogee weirs with hydraulic parameters in both free and submerged flow conditions. Discharge over an ogee weir is related to the length of the weir, upstream total head above the weir crest, and the discharge coefficient. The discharge coefficient is influenced by several factors. In this study, some parameters that influence discharge coefficients of ogee weirs are investigated. These factors include: the weir upstream slope, apron elevation, and downstream submergence. In this regard, ogee weir physical models were fabricated. These models comprise: an ogee weir with a vertical upstream face, ogee weirs with inclined upstream faces (18, 33, and 45 degrees), ogee weirs with downstream apron thicknesses of 3, 5, 7, and 10 cm in free flow and an ogee weir with a vertical upstream slope under submerged flow conditions. Results show that for all ogee weirs, the discharge coefficient (C) increases with increasing P/He, and then remains constant (P is the spillway height and He is the head above the weir crest). The value of the discharge coefficient decreases from 2.25 in free flow conditions to 2.15 with submerged flow conditions. For a constant head over the ogee weirs (He), the discharge coefficient decreases with increasing downstream apron elevation and submergence. The relative discharge coefficient shows a constant trend initially, with increasing hd/He, then later shows a decreasing tendency (hd is the difference between the downstream head and the ogee spillway crest). The threshold value for submergence ratio (hd/He), is 0.75 in the ogee weir in this study. With increasing submergence ratio from 0.75 to 1, the relative discharge coefficient (Cs/C0) decreases from 0.88 to 0.24.